Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12889-020-8187-x
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of sedentary behavior and associated factors among secondary school adolescents in Debre Berhan town, Ethiopia

Abstract: Background: Sedentary life style is becoming increasingly common in this industrial age due to changes on the way people manufacture, transport and communicate. Sedentary lifestyle is associated with chronic diseases (diabetes, cardiovascular disease, and cancer), depression, obesity and premature mortality. The objective of this study was to assess the magnitude and associated factors of sedentary behavior. Methods: School based cross sectional study was conducted among 580 students from April 20 to May 10, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
(15 reference statements)
1
7
0
1
Order By: Relevance
“…Sedentary behavior is characterized by low energy expenditure ( 1 ), whether that behavior is due to leisure or occupation ( 2 ). The increasing availability of modern technology, transportation, and communication systems have exacerbated the problem in low-income countries ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sedentary behavior is characterized by low energy expenditure ( 1 ), whether that behavior is due to leisure or occupation ( 2 ). The increasing availability of modern technology, transportation, and communication systems have exacerbated the problem in low-income countries ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were reported by Gaskin and Orellana in 2018, Mohammed et al in 2020, among Ethiopians, Ahumada et al in 2020, among south Americans. 9,[25][26][27] 1992 income, access to television, and mobile internet, and use of social media were all positively correlated with adolescents' sedentary behavior. 27 Ahumada et al found that living in an urban area, having a high income, smoking or having previously smoked, being physically inactive, owning a computer or notebook at home, and owning a motorized vehicle were significant factors associated with sedentary behavior among Chilean population.…”
Section: Discussionmentioning
confidence: 98%
“…Também foi observada associação entre ECS e maior renda familiar mensal dos participantes, resultados consistentes com outras investigações (de Lucena et al, 2015;Mohammed et al, 2020). Essa relação pode ser explicada devido ao fácil acesso à internet, mídias, aquisição de computadores, smartphones, favorável ao poder aquisitivo, que induzem a maior ECS (Mohammed et al, 2020;Ye et al, 2018).…”
Section: Discussionunclassified